Lesiones pancreáticas de bovinos infestados naturalmente por Eurytrema coelomaticum - Pantiu, Andrea Julia; Aguirre Castro, Laura Sabrina; Avellaneda Cáceres, Agustín; Olmos, Leandro Hipolito; Ovelar, Florencia; Waidelich, M.; Micheloud, Juan Francisco (EEA Balcarce, INTA, 2022)
Poster